Konstruksi Sosial Praktik Turun Waris di Slahung Ponorogo - Amelia Safitri Istiningtyas; Luthfi Hadi Aminuddin (Institut Agama Islam Negeri Ponorogo, 2023)
The successor heirs mentioned in Article 185 of the Compilation of Islamic Law (KHI) Inspres number 1 of 1991 result from the ijtihad of Indonesian mujtahids. From the Compilation of Islamic Law, the existence of grandchildren is recognized. He is a substitute for his parents, who have died first from the heir and legal protection for grandchildren as heirs and acknowledges the position of a substitute heir. As happened in the community in Slahung District, in practice, if a child dies first, then a parent, then the inheritance will be given to his grandson. This research is interesting because the local community does not know the terms related to the replacement heir. The people of the Slahung sub-district named it Turun Waris. The purpose of this research will produce findings to see how the people's thinking and practice of successor heirs in Slahung District with the theory of social construction perspective of Peter Berger and Luckman, which is methodically classified as research with data collected by in-depth interviews, observations and documentation using an externalization process, objectivation, and internalization.